An uplifting outlook for Antarctica - Golledge, Nicholas R (Nature climate change, 2024)
Ice melt from Antarctica is accelerating. Now, a study shows that more realistic treatment of how Earth’s mantle rebounds as Antarctic glaciers retreat can lower projections of mass loss and the associated sea-level rise.